Invitro wholeseedling assay for evaluating nonhost crop plant induction of germination of witch weed seeds - Ahonsi, M.; Emechebe, A. (2005)
Legume-cereal rotation can reduce density of witch weed (Striga hermonthica) seeds in soil. However, legume species and cultivars vary greatly in ability to stimulate germination of S. hermonthica seeds of same or different populations, hence the need for simple method for routine characterisation of these species and cultivars for germination of the parasite seeds. A simple and inexpensive technique, In-vitro whole-seedling assay; was developed and tested for screening non-host crops for ability to stimulate germination of S. hermonthica seeds. In order to compare this new technique with the well established ‘cut-root assay\', sixteen legume cultivars, comprising of seven cowpea (Vigna unguiculata), six soybean (Glycine max), and three groundnut (Arachis hypogea ), in addition to maize (Zea mays L.) hybrids 8338-1 and 9022-13 (used as checks) were screened against three S. hermonthica populations. The new technique was at least as efficacious as the cut-root assay in detecting differences in ability of cultivars of legume crop species to stimulate germination of S. hermonthica seeds. There was less variability in the results obtained in different experimental runs with the new technique, compared with those obtained with the cut root method. The new technique is considered simpler and requires less time, labour and materials. The results obtained for the different legume cultivars screened also suggest that large scale screening of groundnut cultivars for suicidal germination of Striga would be worthwhile in the development of control strategies for the parasite in the region.